Left Ventricular Global Longitudinal Strain in HER‐2 + Breast Cancer Patients Treated with Anthracyclines and Trastuzumab Who Develop Cardiotoxicity Is Associated with Subsequent Recovery of Left Ventricular Ejection Fraction. Issue 4 (16th March 2016) - Fei, Hong‐wen; Ali, Mohammed T.; Tan, Timothy C.; Cheng, Kai‐Hung; Salama, Laura; Hua, Lanqi; Zeng, Xin; Halpern, Elkan F.; Taghian, Alphonse; MacDonald, Shannon M.; Scherrer‐Crosbie, Marielle
Abstract : Aim: The combination of anthracyclines (AC) and trastuzumab (TRZ) is highly effective in patients with aggressive HER‐2 + breast cancer, but has a significant risk of cardiotoxicity (CT). Trastuzumab‐induced CT may be reversible. The aim of this study was to identify echocardiographic parameters associated with recovery of left ventricular ejection fraction (LVEF) in patients who developed CT after AC and TRZ treatment. Methods and Results: Women with newly diagnosed breast cancer treated with AC followed by TRZ and monitored with serial echocardiograms were retrospectively studied. Left ventricular end‐diastolic and systolic volumes, LVEF, and global longitudinal strain (GLS) were examined. Development and reversibility of CT were defined based on changes in LVEF according to the 2014 ASE/EACVI recommendations. Cox analysis was used to determine the association of echocardiographic variables with the subsequent development and reversibility of CT. Ninety‐five patients underwent 5 echocardiograms or more in a 17‐month (13–28 months) follow‐up period. Nineteen patients (20%) developed CT. Left ventricular volumes, LVEF, and GLS measured after AC completion identified the subsequent development of CT. Of the 19 patients with CT, the LVEF partially or fully recovered in 13 (68%). GLS at the time of CT diagnosis was associated with subsequent recovery of LVEF (P = 0.004). Conclusion: In patients with breast cancer treated with AC and TRZ who develop CT, GLS at the time of CT diagnosis is associated with subsequent recovery of LVEF and may be useful for risk stratification and to guide treatment.